Associations of pentraxin 3 with cardiovascular disease and all-cause death: the Cardiovascular Health Study. - Jenny, Nancy Swords; Arnold, Alice M; Kuller, Lewis H; Tracy, Russell P; Psaty, Bruce M (Arterioscler Thromb Vasc Biol, 2009)
OBJECTIVE: We examined associations of pentraxin 3 (PTX3), a vascular inflammation marker, with incident cardiovascular disease (CVD) and all-cause death. METHODS AND RESULTS: 1583 Cardiovascular Health Study participants free of prevalent CVD were included. Nonexclusive case groups were angina (n=476), myocardial infarction (MI; n=237), stroke (n=310), CVD death (n=282), and all-cause death (n=772). 535 participants had no events. PTX3 levels were higher in those with subclinical CVD (1.90+/-1.89 ng/mL) than those without (1.71+/-1.88 ng/mL; P=0.001). Using Cox regression adjusted for age, sex, and ethnicity, a standard deviation increase in PTX3 (1.89 ng/mL) was associated with CVD death (hazard ratio 1.11; 95% confidence interval 1.02 to 1.21) and all-cause death (1.08; 1.02 to 1.15). PTX3 was not associated with angina (1.09; 0.98 to 1.20), MI (0.96; 0.81 to 1.12), or stroke (1.06; 0.95 to 1.18). Adding C-reactive protein (CRP) or CVD risk factors to the models had no significant effects on associations. CONCLUSIONS: In these older adults, PTX3 was associated with CVD and all-cause death independent of CRP and CVD risk factors. PTX3 likely reflects different aspects of inflammation than CRP and may provide insight into vascular health in aging and chronic diseases of aging that lead to death.
Keywords: Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Case-Control Studies; Female; Health Surveys; Humans; Inflammation Mediators; Linear Models; Male; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Serum Amyloid P-Component; Time Factors; United States; Up-Regulation